Development of a wireless sensor for vibration measurement II - Lee, Yu Hui (Nanyang Technological University, 2024)
This final-year project is about the development of wireless vibration sensors. This is important as vibrations may impact the reliability and durability of structures leading to damage and failures. Vibration monitoring is a crucial preventive measure to mitigate these problems. This project aims to compare the Motion Sensor V2 and Rail Sensor which are wireless vibration sensors that the team has made and compare it with other commercially available vibration sensors that use Micro-electromechanical Systems (MEMS) accelerometers to detect vibration levels. The comparison is made through vibration testing using three main methods of testing, Swept Sine Test, Classical Shock Test and Random Vibration Test using an electrodynamic shaker. This project also aims to find ways to improve the Motion Sensor V2 and develop a code to find specific peaks of the on-site data recorded by the Rail Sensor.